Lipoxygenase in singlet oxygen generation as a response to wounding: in vivo imaging in Arabidopsis thaliana - Prasad, Ankush (Sci Rep, 2017)
Wounding, one of the most intensive stresses influencing plants ontogeny and lifespan, can be induced by herbivory as well as by physical factors. Reactive oxygen species play indispensable role both in the local and systemic defense reactions which enable “reprogramming” of metabolic pathways to set new boundaries and physiological equilibrium suitable for survival. In our current study, we provide experimental evidence on the formation of singlet oxygen ((1)O(2)) after wounding of Arabidopsis leaves. It is shown that (1)O(2) is formed by triplet-triplet energy transfer from triplet carbonyls to molecular oxygen. Using lipoxygenase inhibitor catechol, it is demonstrated that lipid peroxidation is initiated by lipoxygenase. Suppression of (1)O(2) formation in lox2 mutant which lacks chloroplast lipoxygenase indicates that lipoxygenase localized in chloroplast is predominantly responsible for (1)O(2) formation. Interestingly, (1)O(2) formation is solely restricted to chloroplasts localized at the wounding site. Data presented in this study might provide novel insight into wound-induced signaling in the local defense reaction.